Correction: Constructing Benchmark Test Sets for Biological Sequence Analysis Using Independent Set Algorithms. - Samantha Petti; Sean R Eddy (PLoS Computational Biology, 2023)
[This corrects the article DOI: 10.1371/journal.pcbi.1009492.].